If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.5(20x + -10) + -2 = 13 Reorder the terms: -0.5(-10 + 20x) + -2 = 13 (-10 * -0.5 + 20x * -0.5) + -2 = 13 (5 + -10x) + -2 = 13 Reorder the terms: 5 + -2 + -10x = 13 Combine like terms: 5 + -2 = 3 3 + -10x = 13 Solving 3 + -10x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -10x = 13 + -3 Combine like terms: 3 + -3 = 0 0 + -10x = 13 + -3 -10x = 13 + -3 Combine like terms: 13 + -3 = 10 -10x = 10 Divide each side by '-10'. x = -1 Simplifying x = -1
| 4x-5x=78 | | -7r-14.5=1/4r | | 5x+20-3x=2x^2+8x | | 3(y+2)+6y=51 | | 20x=32-7x^2 | | 3(6.5+7v)=-22.5 | | 5(2a-6)+2a=66 | | 2x=(12+x)-13 | | (x-3)8=x+25 | | 13(n+4+7m)=equation | | Log(2)(x-2)=4 | | 12n+14=11n-37 | | 8-(3x)=(5x)+8 | | 3k+11z=115 | | 1.2=y-0.22 | | 4x^2+11+12=0 | | 6a-2(4a-5)= | | -5t=-c-2 | | 3x-2(2x-6)=2x-9 | | 4x^2-20x+155=0 | | 6+4x=6+4x | | c=5t-2 | | -24+6y=-6 | | 2+5(6n-1)=-63 | | 6x=57.6 | | 4+x+1=8 | | 3.2x=26.6 | | 1.2=y-0.21 | | -5(m-8)=27-7m | | 2a+7-6a= | | 1-21x=-20-9x | | -8+7n+8n^2=0 |